On the Performance of Electrocatalytic Anodes for Photoelectro-Fenton Treatment of Synthetic Solutions and Real Water Spiked with the Herbicide Chloramben - Salazar-Gonzalez, R (Academic Press, 2018)
The destruction of the herbicide chloramben in 0.050 M Na2SO4 solutions at natural pH has been studied by photoelectro-Fenton with UVA light (PEF). The trials were carried out in a cell equipped with an air-diffusion cathode for H2O2 generation and different electrocatalytic anodes, namely active IrO2-based and RuO2-based electrodes and non-active boron-doped diamond (BDD) and PbO2 ones. Similar removal rates were found regardless of the anode nature because the herbicide was mainly oxidized by [rad]OH formed from Fenton s reaction, which was enhanced by UVA-induced photo-Fenton reaction. The use of an IrO2-based anode led to almost total mineralization at high current density, as also occurred with the powerful BDD anode, since photoactive intermediates originated from [rad]OH-mediated oxidation were degraded under irradiation with UVA light. The good performance of the IrO2-based anode in PEF was confirmed at different current densities and herbicide concentrations. The presence of Cl− in the medium caused a slight deceleration of herbicide removal as well as mineralization inhibition, owing to the production of active chlorine with consequent formation of persistent chloroderivatives. Seven aromatic products along with oxalic and oxamic acids were identified in sulfate medium. Five aromatic derivatives were detected in Cl−-containing matrix, corroborating the generation of organochlorine compounds. In secondary effluent, larger mineralization was achieved by PEF with a BDD anode due to its high oxidation ability to destroy the chloroderivatives, although an acceptable performance was also obtained using an IrO2-based anode. © 2018 Elsevier Ltd